GENERIC STRUCTURE ANALYSES OF TWO AUTHENTIC TEXTS AND THEIR APPLICATIONS IN THE TEACHING OF ENGLISH - Hua, Thi Tin (Đại Học Quốc Gia Hà Nội, 2022)
Systemic functional linguistics provides several tools for analyzing a particular text, one of which is generic structure analysis. As generic competence is extremely important to develop the overall communicative competence, it is necessary for any English language user to achieve genre knowledge. This paper will present a generic structure analysis from a systemic functional perspective of two authentic texts written by native primary school pupils. In addition, based on the analyses of the two texts, some teaching applications will be suggested in this paper in an attempt to promote genre-based language teaching and learning through genre analysis activities in the EFL (English as a Foreign Language) classroom.